Expatriate Adjustment and Managerial Performance : Hotel Management in Malaysia - Chew, Yee Aun (2005)
With the phenomenal growth of hotel development activities in the Asia Pacific region, it is anticipated an increasing need for experienced expatriate managers. When working in a foreign environment, expatriate is faced with challenges from both work related and personal issues. Premature returns and ineffective expatriate performance are crucial issues facing international businesses. This study explored the relationship of expatriate adjustment, managerial performance and human resource management in international hotels located in Malaysia. Using a qualitative approach, the findings suggest that the adjustment factors and process experienced by the expatriate hotel managers is to some extent different from the previous studies. One of the implications identified was the impact of human resource management activities on the expatriate manager’s adjustment and performance. The findings also have identified a number of possible implications for further research and application by the domestic and international human resource practitioners when managing expatriate.